Evaluation of risk stratification strategies in pediatric patients with febrile neutropenia - Keegan Peter Janssens; Cristina Ortiz Sobrinho Valete; André Ricardo Araújo da Silva; Sima Esther Ferman (Elsevier, 2021)
Objective: To evaluate the performance of risk stratification protocols for febrile neutropenia specific to the pediatric population. Methods: Retrospective study of a cohort of pediatric patients undergoing cancer treatment with episodes of neutropenia due to chemotherapy and fever, treated at the emergency department of a tertiary cancer hospital from January 2015 to June 2017. Patients who were bone marrow transplant recipients and patients with neutropenia due to causes other than chemotherapy were excluded. Six protocols were applied to all patients: Rackoff, Alexander, Santolaya, Rondinelli, Ammann 2003, and Ammann 2010. The following outcomes were assessed: microbiological infection, death, ICU admission, and need for more than two antibiotics. The performance of each protocol was analyzed for sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and receiver operator characteristic (ROC) curve. Results: This study evaluated 199 episodes of febrile neutropenia in 118 patients. Microbiological infection was identified in 70 samples from 45 distinct episodes (22.6%), 30 patients used more than two antibiotics during treatment (15%), eight required ICU admission (4%), and one patient died (0.8%). Three protocols achieved high sensitivity indices and NPV regarding the outcomes of death and ICU admission: Alexander, Rackoff, and Ammann 2010; however, Rackoff showed higher sensitivity (0.82) and NPV (0.9) in relation to the microbiological infection outcome. Conclusion: The Rackoff risk rating showed the best performance in relation to microbiological infection, death, and ICU admission, making it eligible for prospective evaluation.